The Trading Volume Impact of Local Bias: Evidence from a Natural Experiment - Jacobs, Heiko; Weber, Martin (Review of Finance, 2012)
Abstract Exploiting regional holidays in Germany as a source of exogenous cross-sectional variation in investor attention, we provide evidence that the well-known local bias at the individual level materially affects stock turnover at the firm level. Stocks of firms located in holiday regions are temporarily strikingly less traded than otherwise very similar stocks in non-holiday regions. This negative turnover shock survives comprehensive tests for differences in information release. It appears particularly pronounced in stocks less visible to nonlocal investors and for smaller stocks disproportionately driven by retail investors. Our findings contribute to research on local bias, trading activity, and investor distraction.